2023
DOI: 10.1002/adma.202304638
|View full text |Cite
|
Sign up to set email alerts
|

Mechano‐Activated Cell Therapy for Accelerated Diabetic Wound Healing

Yufeng Shou,
Zhicheng Le,
Hong Sheng Cheng
et al.

Abstract: Chronic diabetic wounds are a significant global healthcare challenge. Current strategies, such as biomaterials, cell therapies, and medical devices, however, only target a few pathological features and have limited efficacy. We developed a powerful platform technology combining magneto‐responsive hydrogel, cells, and wireless magneto‐induced dynamic mechanical stimulation (MDMS) to accelerate diabetic wound healing. Our hydrogel encapsulates FDA‐approved fibroblasts and keratinocytes to achieve ∼3‐fold better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…At present, there are three main physical factors: temperature, and exogenous stimuli (light, electric, ultrasonic and magnetic field). 47 4.3.1. Temperature-responsive Systems.…”
Section: Ph-responsive Systemsmentioning
confidence: 99%
“…At present, there are three main physical factors: temperature, and exogenous stimuli (light, electric, ultrasonic and magnetic field). 47 4.3.1. Temperature-responsive Systems.…”
Section: Ph-responsive Systemsmentioning
confidence: 99%
“…24,25 Up to now, the definite mechanisms of poor diabetic wound healing are not yet well understood, but the unbalanced inflammatory response, oxidative stress effect, high blood glucose level, lack of angiogenesis and extremely high risk of bacterial infection are recognized as the primary reason for the lasting wounds. 26,27 Thus, antibiotics, growth factors, cells, and other biologically active substances are usually introduced into a hydrogel to realize precise and extended regulation of the wound microenvironment, which is anticipated to accelerate the healing of wounds. Indeed, the constructed compound hydrogels could meet the requirements of wound healing and n u m e r o u s i n n o v a t i v e s t u d i e s h a v e b e e n r eported.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the constructed compound hydrogels could meet the requirements of wound healing and n u m e r o u s i n n o v a t i v e s t u d i e s h a v e b e e n r eported. 1,10,15,16,18,21,22,26,28,29 However, clinical researchers continually referred to the involvement of drug carriers significantly influencing the biocompatibility, biodegradability, and loading efficacy and having some potential side effects. Additionally, these compound hydrogels usually require complex synthesis and are relatively expensive, which significantly impede effective clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of fibroblasts to myofibroblasts is a critical step during the wound healing process. Compared with fibroblasts, myofibroblasts are characterized by the expression of high levels of α-SMA that form contractile bundles and generate large cellular tractions to support wound closure. , It has been reported that the myofibroblast transition is promoted by soluble factors such as TGF-β and by mechanical forces as well. , Taking the NIR light and thermal responsive properties of PIC/CM@NPs hydrogel composites into consideration, we characterized the temperature and stiffness changes after NIR irradiation. CM@NPs slightly exhibit a photothermal effect that partially converts light into heat, leading to an approximate 4 °C increases from 37 to 41 °C under NIR for 150 s (Figure S7).…”
mentioning
confidence: 99%
“…36,37 It has been reported that the myofibroblast transition is promoted by soluble factors such as TGF-β and by mechanical forces as well. 36,38 Taking the NIR light and thermal responsive properties of PIC/CM@NPs hydrogel composites into consideration, we characterized the temperature and stiffness changes after NIR irradiation. CM@NPs slightly exhibit a photothermal effect that partially converts light into heat, leading to an approximate 4 °C increases from 37 to 41 °C under NIR for 150 s (Figure S7).…”
mentioning
confidence: 99%